Hak Cipta Sebagai Jaminan Fidusia - Puspitasari, Rina (JIPRO: Journal of Intellectual Property, 2021)
This research was conducted to assess the implementation of Article 16 paragraph (3) of Law Number 28 Year 2014 states that copyright can be used as an object of fiduciary guarantee. The the problem statement are: first, could a copyright can be categorized as an asset for the Authors and/or Copyright Holder in accordance with Article 16 paragraph (3) of Law No. 28 of 2014 concerning Copyright? Second, could copyright be determined as an asset for Authors and/or copyright holders which could be guaranteed as fiduciary rights? Third, how is the authority of a Notary in implementing Copyright as a Fiduciary Guarantee? The results of the research show that a copyright guaranteed by fiduciary can be executed for the execution of Article 29 of Law Number 42 of 1999 about Fiduciary the reason is the economic right of the copyright could be secured (it is an intangible object). Besides, related to the Notary, the authority of the Notary to make burden of fiduciary deed has already been mentioned on the Article 5 Section (1) about Fiduciary, thus there is no reason for the Notary to reject for creating deed of fiduciary with copyright as the object.